Manajemen Kurikulum Sekolah Khas dalam Membentuk Karakter Al-Qur'an dan Kemandirian Ekonomi Siswa - Aisyah, Siti; santosa, Achadi Budi Santosa (Perspektif Pendidikan dan Keguruan, 2024)
A distinctive curriculum is an important factor in supporting educational success, especially for superior schools having a distinctive curriculum is quite attractive branding. The aim of this research is to reveal how strategic management encourages the realization of schools with distinctive curricula. The method used in this research is a qualitative method with a case study approach. Data collection techniques were carried out through unstructured in-depth interviews, observation and documentation. Data validation was carried out through triangulation of data sources in the form of focus group discussions. The research results show that (1) The typical curriculum has been formulated by referring to the vision, mission and goals of the school, determining achievement targets based on the PPDB selection formation and effective target achievement strategies; (2) Implementation of a typical curriculum begins with determining personnel and distributing teaching duties as well as preparing a coordinated schedule; (3) the program implementation process is supported by the role and participation of stakeholders as well as the use of information technology; (4) Assessments are carried out both routinely and at the end of the program to minimize errors accumulating at the end of the program. Efforts to improve the program are carried out by considering impacts and prioritizing results.